PERSPEKTIF NEUROBIOLOGI KORBAN KEKERASAN SEKSUAL DAN TANGGUNG JAWAB MORAL DALAM ISLAM (MINI REVIEW) - Hafsan, Hafsan; Firdaus, Firdaus; Pratiwi, Afryanti (Universitas Islam Negeri Alauddin Makassar, 2025)
Sexual violence on university campuses represents a multidimensional crisis that violates not only moral integrity but also inflicts deep and lasting biological damage on survivors. Neurobiological research reveals that trauma from sexual violence can alter the structure and function of the brain, particularly the amygdala, hippocampus, and prefrontal cortex which are critical for emotional regulation, memory, and decision-making. Disruptions in these brain systems may lead to long-term conditions such as dissociation, chronic anxiety, and post-traumatic stress disorder (PTSD). In the Indonesian academic context, sexual violence often remains concealed behind institutional hierarchies, power imbalances, and a normalized culture of silence, as reflected in various studies and official reports. This article integrates findings from neuroscience with Islamic ethical principles to formulate a holistic approach to victim protection and recovery. Islam, through the framework of maqāṣid al-sharī‘ah, upholds personal dignity (al-‘irḍ) as a fundamental value that must be safeguarded. Social responsibility to protect survivors and prevent injustice is strongly emphasized in the Qur'an and prophetic tradition. Thus, the Islamic response to sexual violence goes beyond legalism, encompassing spiritual, biological, and psychosocial dimensions. In this view, an integrative framework combining scientific insight and moral-spiritual values is essential to build a just, compassionate, and trauma-informed response to sexual violence on campus. Kekerasan seksual di lingkungan kampus merupakan krisis multidimensi yang tidak hanya mencederai integritas moral, tetapi juga meninggalkan dampak biologis yang mendalam bagi korban. Kajian neurobiologi menunjukkan bahwa trauma akibat kekerasan seksual dapat mengubah struktur dan fungsi otak, terutama pada area seperti amigdala, hipokampus, dan prefrontal cortex, yang berperan dalam pengaturan emosi, memori, dan pengambilan keputusan. Gangguan pada sistem saraf ini tidak jarang menghasilkan gejala jangka panjang seperti disosiasi, kecemasan kronis, dan gangguan stres pascatrauma (PTSD). Dalam konteks akademik di Indonesia, kasus-kasus kekerasan seksual sering tersembunyi di balik relasi kuasa, hierarki institusional, dan normalisasi budaya diam, sebagaimana terbaca dalam sejumlah laporan riset dan catatan lembaga negara. Artikel ini memadukan temuan-temuan ilmu saraf dengan etika Islam untuk merumuskan pendekatan holistik dalam perlindungan dan pemulihan korban. Islam, melalui kerangka maqāṣid al-syarī‘ah, menempatkan kehormatan (al-‘irḍ) sebagai nilai yang harus dijaga secara serius. Tanggung jawab sosial untuk melindungi korban dan mencegah kezaliman ditegaskan dalam ajaran Al-Qur’an dan hadis. Maka, penanganan kekerasan seksual dalam kerangka Islam tidak hanya bersifat legalistik, tetapi juga menyentuh aspek spiritual, biologis, dan psikososial secara integral. Dengan demikian, dibutuhkan integrasi antara sains dan nilai moral sebagai fondasi respons yang lebih adil, manusiawi, dan menyembuhkan.